Study of proton radiation effect to row hammer fault in DDR4 SDRAMs. (January 2018) - Lim, Chulseung; Park, Kyungbae; Bak, Geunyong; Yun, Donghyuk; Park, Myungsang; Baeg, Sanghyeon; Wen, Shi-Jie; Wong, Richard
Abstract: This paper shares the effects of row hammer fault through high-energy proton radiation. The significance of row hammer fault is highlighted in terms of two different technologies in DDR4 SDRAM. Row hammer stress prevents nearby storage cells from maintaining storage data within the retention time of 64-ms. The stress is worsened by the radiation damage in silicon due to the high-energy particles. Proton-based radiation damage tests were performed with DDR4 SDRAM components from two different technologies. Experiment results showed that after proton irradiation, the number of bit errors caused by the row hammering test increased about 41% and 66% in technologies 2x-nm and 2y-nm, respectively. With 2y-nm technology, bit errors started to appear from 5 K Number of Hammering (NHMR )—the equivalent of 500-μs retention time. For 2y-nm components, more than 90% of failed words had multiple failed cells, which could not be corrected by Single Error Correction and Double Error Detection (SEC-DED) codes. Highlights: The row hammering tests with two different technologies of DDR4 SDRAMs are presented. As technology shrinks, the number of failed cells by row hammer increased. The radiation damage by high energy proton accelerates the row hammer-induced failure. In the worst case after proton irradiation, the failure in 2x-nm technology occurred at 5 K NHMR .